1998
DOI: 10.1002/(sici)1097-4628(19980502)68:5<727::aid-app5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of holding power in the blends of poly(butyl acrylate) with poly(vinylidene fluoride-cohexafluoro acetone)

Abstract: Shear adhesion of pressure‐sensitive adhesive tapes was evaluated for the blends of poly(butyl acrylate) with poly(vinylidene fluoride‐co‐hexafluoro acetone). The shear adhesion was determined as the function of the shear strain of pressure‐sensitive adhesive tape against elapsed time under the shear stress. Shear adhesion of the blends increased with increasing poly(vinylidene fluoride‐co‐hexafluoro acetone) content. Experimental shear strain data were characterized with dynamic viscosity, stress and shear ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Theoretical modeling of non-crosslinked PSAs behavior in the static shear test predicting the time to failure of the adhesive joint on the basis of rheological measurements was performed by Zosel [6] and Kano et al [46]. It was found that the model predicts the time to failure for low molecular weight PIB fairly well, whereas it underestimates the experimental results for high molecular weight polymer.…”
Section: Modelingmentioning
confidence: 99%
“…Theoretical modeling of non-crosslinked PSAs behavior in the static shear test predicting the time to failure of the adhesive joint on the basis of rheological measurements was performed by Zosel [6] and Kano et al [46]. It was found that the model predicts the time to failure for low molecular weight PIB fairly well, whereas it underestimates the experimental results for high molecular weight polymer.…”
Section: Modelingmentioning
confidence: 99%
“…The reproducibility of the peel test is signi cantly affected by several factors such as temperature, humidity, and peel rate. Because of the complications, in the use of these methods, sometimes large experimental uncertainties as well as the qualitative nature of data must be tolerated [12,13]. Eventually, this will hinder the optimization of PSA properties via tailoring of molar mass, crosslink density, and the amount/ type of adhesion promoters.…”
Section: Introductionmentioning
confidence: 99%